METHODS OF TEACHING EXPRESS READING TEXT IN LITERATURE CLASSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The relevance of the formation of literary competence in students in this article; requirements for the expressiveness of the teacher's and student's speech in education; ideas on how to teach prose, poetry, drama to expressive reading.